Functional Properties and Molecular Architecture of Leukotriene A4 Hydrolase, a Pivotal Catalyst of Chemotactic Leukotriene Formation - Jesper Z. Haeggström; Pär Nordlund; Marjolein M.G.M. Thunnissen (The Scientific World Journal)
The leukotrienes are a family of lipid mediators involved in inflammation and allergy. Leukotriene B4 is a classical chemoattractant, which triggers adherence and aggregation of leukocytes to the endothelium at only nM concentrations. In addition, leukotriene B4 modulates immune responses, participates in the host defense against infections, and is a key mediator of PAF-induced lethal shock. Because of these powerful biological effects, leukotriene B4 is implicated in a variety of acute and chronic inflammatory diseases, e.g., nephritis, arthritis, dermatitis, and chronic obstructive pulmonary disease. The final step in the biosynthesis of leukotriene B4 is catalyzed by leukotriene A4 hydrolase, a unique bifunctional zinc metalloenzyme with an anion-dependent aminopeptidase activity. Here we describe the most recent developments regarding our understanding of the function and molecular architecture of leukotriene A4 hydrolase.